Exploration of solute-solvent interactions in aqueous mixtures of monosaccharides and triammonium citrate (TAC) at different temperatures: Volumetric and acoustic approach. (December 2019) - Kumar, Harsh; Sharma, Monisha; Kumar, Vaneet
Highlights: Densities and speeds of sound for D (+) -xylose and D (−) ribose in aqueous TAC solutions. Positive apparent molar volumes predicts dominance of solute-solvent interactions. Positive transfer volumes predicts ion-ion interactions in the mixtures. Pair wise interactions in saccharides + water + TAC mixtures. Abstract: The present study reports the densities, ρ and speeds of sound, u of monosaccharides (D (+) -xylose and D (−)-ribose) in aqueous triammonium citrate (TAC) solutions at temperatures, T  = (288.15, 298.15, 308.15 and 318.15) K and at experimental pressure, p  = 0.1 MPa. The available data is used to calculate the thermophysical parameters like apparent molar volumes V ϕ, apparent molar isentropic compressibilities K ϕ, s, partial molar volumes, V ϕ o and partial molar isentropic compressibilities, K ϕ, s o and then the partial molar volumes of transfer, Δ V ϕ o and partial molar isentropic compression of transfer Δ K ϕ, s o are evaluated. Further, the expansion coefficients, (∂Vϕ 0 /∂T) p, (∂ 2 Vϕ 0 /∂ 2 T) p, pair ( V AB, K AB ) and triplet ( V ABB, K AB B ) interaction coefficients have also been determined. These parameters have been discussed to ascertain the solute co-solute interactions. Apparent specific volumes ASV and hydration numbers N w are also calculated to check the taste behaviour and hydration behaviour respectively.